Kuwait : Staff Report for 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Kuwait's 2006 Article IV Consultation reports that its macroeconomic performance has been strong in recent years reflecting sharply higher oil and non-oil activity. Over the medium term, Kuwait's financial position is projected to remain strong. The large external current account and fiscal surpluses are expected to lead to a buildup of a large stock of financial assets for future generations. However, GDP growth is expected to slow down unless the pace of structural reforms accelerates.